Use of Demonstration Experiments in Teaching Molecular Physics in General Secondary Schools - Dehqonova Dehqonova; Yakubova Yakubova; Alisherova Alisherova (International Journal of Educational Narratives, 2025)
Background. The topics of the molecular physics department study the main fundamental demonstration experiments that confirm the existence of atoms and molecules and their movement. Purpose. These experiments make it possible to determine physical quantities such as the size, mass, speed and concentration of atoms and molecules. The existence of atoms and molecules is no longer just a hypothesis, but is concrete evidence confirmed by the experimental and practical activities of people. Method. In school conditions, it is an important educational task to provide new knowledge using experimental methods with the help of available tools and equipment to form these facts in the minds of students. Results. Also, experiments are important for a deeper explanation of the theory in topics such as hydrostatic pressure and pressure transmission in liquids. Conclusion. The article deepens the theoretical foundations of molecular physics and hydrostatic pressure, highlights the role of demonstration and laboratory experiments in teaching these topics, and provides information about modern experiments.